Government communication as a means to combat disinformation in Spain and Flanders: the case of Covid-19 - Vandecraen, Evelien; Vangehuchten, Lieve; Fernández Vallejo, Ana María (Círculo de Lingüística Aplicada a la Comunicación, 2025)
The COVID-19 crisis was accompanied by an “infodemic” of disinformation on an unprecedented scale. Governments had to tackle the detrimental effects of disinformation on society by adopting various communicative strategies. This study uses a critical discourse analysis to investigate to what extent and in what ways government communication campaigns promoting corona vaccination in Flanders and Spain interacted with disinformation. First, the regional determinants of disinformation are considered, along with important theories and strategies of government and health communication. Consequently, a limited analysis of disinformation in Spain and Flanders is completed, followed by an analysis of the communication campaigns to observe whether the strategies were applied in the campaigns and adapted to the sociocultural reality. The analysis indicates that the materials did interact with disinformation but that the strategies were only partly adapted to the context of the regions. It is concluded that governments need a deeper understanding and awareness of the nature of disinformation and its consequences on the population. This awareness allows to efficiently adapt communication campaigns and effectively fight disinformation through government communication.